PENGARUH PEMBERIAN AMPAS TEH DAN PUPUK NPK TERHADAP PERTUMBUHAN BIBIT TANAMAN KOPI ARABIKA (Coffea arabica L.) - Pangihutan, Prengki Eben; Yetti, Husna; Isnaini, Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The aim of research were determine the effect interaction of tea dregs and NPK fertilizer application obtain the best dose for the growth of coffee arabica seedlings. The experiment was established at experimental farm Â of the Faculty of Agriculture, University of Riau, in Pekanbaru, from September 2016 to January 2017. The research arranged experimentally by using Completely Randomized Design. The first factor tea dregs was four levels of 0, 60, 120 and 180 g/polybag and the second factor NPK fertilizer was three level of 0, 10, 15 g/polybag. Combination treatment was repeated 3 times. Parameters measured were plant height, number of leaves, root volume, root dry weight and root crown ratio. The data was analyzed statistically and followed by DNMRT at 5% level. The result showed the effect of tea dregs dose of 180 g/polybag significantly to all treatment except root crown ratio, while fertilizers NPK dose of 15 g/polybag significantly increased plant height, root volume and root dry weight. Interaction of tea dregs dose of 180 g/polybag and fertilizers NPK dose of 15 g/polybag significantly increased root volume and root dry weight.Â Keywords: Coffee arabica seedling, tea dregs, fertilizers NPK